Labour's loves? Isabella Whitney, Leonard Wheatcroft and the love miscellany. Issue 8 (14th September 2019) - Wiseman, Susan
ABSTRACT: This essay investigates the place of non-elite makers of miscellanies in print and manuscript. It analyses the parts of Richard Jones and Isabella Whitney in shaping Copy of a Letter (1567) and Leonard Wheatcroft's mid-seventeenth-century manuscript miscellany, 'Cum ye gallants' to ask how these miscellanists and poets used the material available to them to explore love. The essay argues for a reconsideration of the assumption that non-elite miscellanists had a socially aspirational relationship to the genre of the miscellany and suggests that they rather used cultural resources to enunciate the issues of their own world.